1997
DOI: 10.3354/meps158121
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance and gap formation in a marine benthic mosaic:influence of shifting macroalgal patches on seagrass structure and mobile invertebrates

Abstract: A field experiment was used to examine the interactions among structurally complex, spatially shifting structure (macroalgae deposited by currents), less-complex stationary structure (seagrass), and mobile benthic invertebrates. I tested the effect of drift algal patches on underlying seagrass structure and fauna by establishing manipulated algal mats over seagrass for comparison with control seagrass plots. Control and experimental plots did not differ significantly for any variable prior to algal addition, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 46 publications
3
75
2
Order By: Relevance
“…This variability likely resulted from patchiness associated with the bloom deposition in our mesocosms or heterogeneity in the sediment microbial communities. Similar patchiness has been observed in field studies (Holmquist 1997, Sfriso & Marcomini 1999. Despite the observed variability, our statistical analyses confirmed that bulk isotopic enrichments at the end of the experiment (Days 7 & 14) were higher than at the beginning of the experiment (Days 1 & 2) for both lagoons, demonstrating accumulation and retention of macroalgal 13 C and 15 N in the sediments following the simulated die-off.…”
Section: Label Incorporation Into Bulk Sedimentssupporting
confidence: 71%
“…This variability likely resulted from patchiness associated with the bloom deposition in our mesocosms or heterogeneity in the sediment microbial communities. Similar patchiness has been observed in field studies (Holmquist 1997, Sfriso & Marcomini 1999. Despite the observed variability, our statistical analyses confirmed that bulk isotopic enrichments at the end of the experiment (Days 7 & 14) were higher than at the beginning of the experiment (Days 1 & 2) for both lagoons, demonstrating accumulation and retention of macroalgal 13 C and 15 N in the sediments following the simulated die-off.…”
Section: Label Incorporation Into Bulk Sedimentssupporting
confidence: 71%
“…Decreased grass-shrimp abundances in response to trampling, particularly for Thor manningi, were probably the result of the decrease in seagrass physical complexity. As trampling slowly thinned the seagrass, shrimps probably emigrated to denser seagrass outside the trampling lanes, or failed to immigrate into the trampling lanes rather than suffering direct mortality (see also Holmquist 1997, Keough & Quinn 1998, Brown & Taylor 1999. Conversely, shrimps of the family Processidae are often associated with bare patches in seagrass meadows (Holmquist pers.…”
Section: Discussionmentioning
confidence: 99%
“…Algal epiphytes can increase the complexity of aquatic macrophytes, resulting in greater diversity of the associated mobile species (Holmquist, 1997;Jernakoff and Nielsen, 1998). Similarly, the presence of colonial organisms such as sponges, hydrozoans, and bryozoans can increase macrophytic complexity (Hall and Bell, 1988).…”
Section: Introductionmentioning
confidence: 99%